The fate of CD4+ T cells under tolerance‐inducing stimulation: a modeling perspective. Issue 10 (22nd October 2013) - Caridade, Marta; Oliveira, Vanessa G; Agua‐Doce, Ana; Graca, Luis; Ribeiro, Ruy M
Abstract : Non‐depleting anti‐CD4 monoclonal antibodies (MAbs) induce long‐term dominant tolerance mediated by regulatory T cells in several animal models of transplantation, allergy and autoimmunity. However, despite many studies on tolerance induction following CD4 blockade, the consequences of this intervention on T‐cell kinetics are still unknown. Mathematical models have been useful to understand lymphocyte dynamics, estimating rates of proliferation and cell death following an intervention. Using the same strategy, we found that CD4 + T cells activated in vitro in the presence of non‐depleting anti‐CD4 MAbs are prevented from undergoing optimal proliferation and show a higher frequency of apoptosis. Although the changes are small, during the course of a proliferative response, they lead to very distinct final levels of cell numbers. The importance of these mechanisms, predicted by the mathematical model, was validated by showing that lck‐driven Bcl‐xL transgenic mice, bearing T cells resistant to apoptosis, fail to become tolerant to skin grafts following CD4‐blockade. Our data show that, in addition to induction of regulatory T cells, CD4 blockade has a marked effect in the effector T‐cell pool by the combined action of hindering proliferation while favoring apoptosis. It is, therefore, the combination of all those mechanisms that leads to stable tolerance.